2011
DOI: 10.1016/j.jpor.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a dental color analysis system: The Crystaleye Spectrophotometer®

Abstract: The Crystaleye Spectrophotometer(®) is an easy-to-use color analysis system producing accurate color measurements under clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…Their basic structures and measuring principles have been studied and compared previously [2]. Spectrophotometric measurements have been proved to outperform visual assessments in both reliability and reproducibility [16][17][18][19], and they are the gold standard of color measuring devices [12]. However, it has been demonstrated that both spectrophotometric and colorimetric devices can suffer edge loss effects, which happen when a device with a small window measuring a transparent material results in light scattering to the edge of the sample without being detected.…”
Section: Introductionmentioning
confidence: 99%
“…Their basic structures and measuring principles have been studied and compared previously [2]. Spectrophotometric measurements have been proved to outperform visual assessments in both reliability and reproducibility [16][17][18][19], and they are the gold standard of color measuring devices [12]. However, it has been demonstrated that both spectrophotometric and colorimetric devices can suffer edge loss effects, which happen when a device with a small window measuring a transparent material results in light scattering to the edge of the sample without being detected.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the Vita system Vita Toothguide 3D‐Master classifies a logical selection of color into hue, value, and chroma. Every color was represented as a unique point in the axes of the CIELAB system …”
Section: Discussionmentioning
confidence: 99%
“…37 In clinical dentistry, it is difficult to evaluate tooth color under ideal conditions, and it is useful to use a color measuring device that produces constant values under any given condition. 38 Understanding the influence of different variables such as hue, value, and chroma in shade selection where light illumination on a tooth and how the eye interprets these values has an influence can assist in shade selection. The use of the Vita system Vita Toothguide 3D-Master classifies a logical selection of color into hue, value, and chroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Em virtude da subjetividade associada aos métodos de seleção visual da cor, foram lançados para o mercado sistemas eletrónicos baseados em aparatologias espectrofotométricas ou colorimétricas, visando obter determinações reprodutiveis. 1,25 Estes aparelhos baseiam -se na aquisição da cor através do sistema de cores CIE L*a*b*, convertendo a medição numa escala contínua de valores, sendo depois traduzidos nos códigos das escalas, tornando seleção da cor mais fácil e objetiva. 17,20,22,26,27 Estes aparelhos de medição de cor podem ter diferentes sistemas de leitura: medição por ponto, como VITA a b s t r a c t…”
Section: Introductionunclassified